THE EFFECT OF INCENTIVES AND WORKLOAD ON EMPLOYEE PERFORMANCE AT PT. TROPICA MAS PHARMACEUTICALS SUMATERA REGION I - Rizka Hanazohie; Yasmin Safira Adhies; Suyono (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2023)
The purpose of this study was to determine the effect of incentives and workload on employee performance at PT. Tropica Mas Pharmaceuticals Regional Sumatra I. The population and sample in this study were 35 people. The measuring instrument used was a questionnaire containing 55 statements consisting of 20 incentive statements, 15 workload statements and 20 employee performance statements. Data analysis using the t test, F test, and the coefficient of determination. The results of the incentive t test study obtained a sig value of 0.028 <0.05, so incentives have a significant effect on employee performance, while workload has a sig value of 0.188> 0.05, so workload has no significant effect on employee performance. The results of the F test obtained a sig value of 0.005 <0. 05 so that incentives and workload have a significant effect on employee performance. The result of the coefficient of determination is 0.237, meaning that 23.7% of the variable variation is explained by incentive and workload variables, while the remaining 76.3% is explained by other variables not examined.